Commuting time and labour supply: A causal effect? - José Ignacio Giménez; José Alberto Molina (Institute for the Study of Labor (IZA), 2011)
We analyze the causal effect of the length of the worker's commute on worker's productivity, by examining whether commuting time has any effect on worker's labour market supply. Using the Spanish Time Use Survey 2002-03, our GMM/IV estimation yields a positive causal impact of commuting time on the time devoted to the labour market, with one hour of commuting increasing the time devoted to the labour market by 35 minutes in a working day. Our results shed light on the relationship between commuting and workers behaviour, since daily labour supply should be considered in theoretical models to provide a comprehensive view of commuter behaviour.
urn:nbn:de:101:1-201104114033
Keywords: R23; J22; J24; 330; commuting; labour supply; productivity; causality; Time Use Survey; Pendelverkehr; Arbeitsangebot; Arbeitsproduktivität; Zeitverwendung; Spanien